Analysis of factors that influence the initial reading and writing learning of grade 1 students at SDN Mlaten 1 - Aqidatul Izza TPP; Ena Yayuk; Innany Mukhlishina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The initial reading and writing learning, early reading and writing (MMP) learning, is essential for primary students, including grade 1 students at SDN Mlaten 1. MMP's ability needs to be mastered so that students can absorb the material taught by the teacher and provide preparation for the next grade level. The low ability of grade 1 students at SDN Mlaten 1 to read and write at the beginning can be influenced by various factors, including internal and external factors. This research analyses the factors that influence initial reading and writing (MMP) learning for grade 1 students at SDN Mlaten 1. This research was conducted at SDN Mlaten 1 in the even semester of the 2022/2023 academic year, from February 21 - March 1, 2023. A 1st-grade teacher and 29 grade 1 students were the subjects of this research. This study collects data through observation, interviews, and documentation. Intellectual ability, enthusiasm, and willingness to study all impact pupils' early reading and writing skills. Aside from this, other elements such as the teacher's ability to teach, learning media, and parents' attentiveness to their children also influence kids' reading skills.